Critical Analysis of Differentiated Learning Implementation on Science Literacy and Creativity in Elementary School Students - Ari Parwati; Subuh Anggoro (UM Purwokerto Press, 2025)
This study critically analyzes the implementation of differentiated learning in improving science literacy and creativity among elementary school students. Through a qualitative literature review approach, various research findings were synthesized, demonstrating that differentiated learning, especially when combined with the Problem-Based Learning (PBL) model, significantly enhances student outcomes. The results indicate improvements in literacy, numeracy, critical thinking, and creative skills when learning is tailored to students' interests, readiness, and learning profiles. Differentiated learning not only addresses the diversity of student needs but also fosters active engagement and innovation in the classroom. The findings support the integration of differentiated strategies in science education to build foundational 21st-century competencies among young learners.